FATHER ABSENCE AND LIFE HISTORY STRATEGY OUTCOMES AMONG MALAYSIAN WOMEN: AN ALMOST ‘EMPTY’ SYSTEMATIC LITERATURE REVIEW (Jurnal Pembangunan Sosial, 2022)
Understanding about the life history strategy (LHS) of Malaysian women who experienced father absence (FA) during childhood islimited. This systematic literature review (SLR) pursued a narrative synthesis methodology to investigate the links between FA and sixlife history (LH) decision-nodes constitutive of an individual’s LHS: pubertal timing, number of offspring, first marriage timing, first birth timing, sexual debut age, and sexual partner count in the Malaysian female population. It investigated if these decision-nodes clustered together to lie predictably on the slow-to-fast continuum. On July 17, 2022, APA PsycARTICLES, ICTRP, MEDLINE, CINAHL, ProQuest, CT.gov, Scopus, and Embase were searched for studies published prior to December 2021. One cross-sectional study, involving 567 women was found relevant. The review found that FA at any time in childhood was not linked with pubertal age or number of offspring but only FA experienced during late childhood, not early childhood was associated with a swifter age of getting married and giving birth for the first time. It found that FA did not provoke a grouping of LH decision-nodes that were describable as ‘slow’ and ‘fast’. The review yielded no results on how FA relates to sexual debut age and sexual partner count. The Crowe Critical Appraisal Tool (CCAT) examined risk of bias and found the study to be low-risk. These findings have implications for LH decision-making research, fathering research, extant theories on fathers’ influence on daughters’ psychosexuality, LH theory’s postulation of a slow-to-fast continuum, Malaysian family policies, and Malaysian daughters from father-absent homes.